Depresión por abuso sexual y su repercusión en el estado emocional de una adolescente de 12 años del cantón Babahoyo - Cabero Diaz, Elias Samuel (2021)
In the present case study, the topic Depression due to sexual abuse and its impact on the emotional state of a 12-year-old adolescent, a resident of the Babahoyo canton, Los Ríos province, was obtained. through interviews and a psychological instrument such as the person in the rain projective test, which was performed directly on the patient. Based on the results obtained, a mild depressive disorder was detected with a code of F32.0 according to CIE 10. The experience of sexual abuse and the dramatic family events that were experienced brought distortions to the adolescent about her self-concept, the world and the world. future. For this reason, a therapeutic scheme was implemented, with a cognitive behavioral base, which helped to recognize the negative thoughts that she had towards herself and that caused clinically significant discomfort, this allowed the patient to restructure this thinking with the help of the techniques used and to reinforce her self-esteem in such a way his emotional state managed to improve.